Analisis Momen Tensor dan Mekanisme Fokus Gempa di Sumatera Barat Menggunakan Metode Inversi Waveform - Putri, Zakiah Putri; Syafriani; Akmam; Letmi Dwiridal (Universitas Islam Negeri Alauddin Makassar, 2024)
Analysis of the tensor moment and focal mechanism of an earthquake aims to determine the value of the tensor moment that represents the direction of the force that causes the earthquake and the focal mechanism that describes the characteristics of the fault motion that causes the earthquake. Analysis of the tensor moment and focal mechanism is carried out using the waveform inversion method. The waveform inversion method is an inversion method that utilizes the P-wave arrival time and is estimated with a Green's function involving three seismogram components. The data used in this study are ten earthquake data in the West Sumatra region in 2007-2022 whose earthquake sources are in the Sumatra fault zone with earthquake strength ≥4.9 Magnitude. The results of this study obtained a range of tensor moment values, namely M11 = -2.595 to -4.555, M22 = 1.743 to 4.476, M33 = 0.853 to 0.079, M12 = 6.258 to -4.814, M31 = 1.241 to 0.719, M32 = 0.530 to -1.436, and the results of the focus mechanism obtained are strike-slip patterns.